The experience in Uruguay of the Rural Development Forum in family farming territories - Arbeletche, Pedro Raul (2019)
ABSTRACT  The MDRs (Rural Development Forum) were created in Uruguay in 2011 with the process of decentralization of the MGAP (Ministry of Livestock, Agriculture and Fisheries). Based on a territorial and participatory rural development approach, this public policy seeks to consolidate and favor the permanence of family farming in the rural territories of the country. The objective of this paper is to characterize the operation and the territorial contribution of the MDRs in three departments (Río Negro, Rivera and Salto). The methodology consisted of applying an analysis guide in the MDRs of the three departments through individual and collective interviews, supplemented by documental and bibliography review. The results show that the policy allowed to move from a sector treatment to an inter-sector and territorial approach, where the demands for basic social services are very important and always present, surpassing the technical-productive requirements. Beyond the heavy dependence of the MGAP coordination, in each territory, the MDRs strengthened the local institutions, increasing the role of the family farming organizations in the consolidation of the strategies of the producers and employees.